2013
DOI: 10.1111/acfi.12026
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ownership structure, analyst following and institutional infrastructure on stock price informativeness: international evidence

Abstract: Using firms from 20 non‐US countries, we investigate whether and how ownership structure, analyst following and country‐level institutions influence stock price informativeness (SPI). We find that stock price informativeness decreases with control‐ownership wedge (the detachment of voting rights from cash flows rights), and this SPI‐reducing effect of the wedge is attenuated for firms with high analyst following and in countries with strong country‐level institutions. We also find that stock price informativen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…Although at lower levels of ownership concentration, our results are consistent with the entrenchment hypothesis, which complements the findings of Jiang et al (2014) and Boubaker et al (2014), at higher ownership levels, the results are consistent with the incentive alignment hypothesis, supporting the finding of Brockman and Yan (2009). These findings provide evidence on the role of banks' ownership structure in explaining the variations in their stock returns and thus contribute to better understanding the importance of corporate governance in concentrated ownership environments for the banking industry.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although at lower levels of ownership concentration, our results are consistent with the entrenchment hypothesis, which complements the findings of Jiang et al (2014) and Boubaker et al (2014), at higher ownership levels, the results are consistent with the incentive alignment hypothesis, supporting the finding of Brockman and Yan (2009). These findings provide evidence on the role of banks' ownership structure in explaining the variations in their stock returns and thus contribute to better understanding the importance of corporate governance in concentrated ownership environments for the banking industry.…”
Section: Discussionsupporting
confidence: 91%
“…Next, we follow the same procedure as used by Morck et al (2000) and control for synchronicity in firm fundamentals by including a proxy for earnings comovement. To capture the comovement, we first estimate R 2 in each year and the total sum 10 Empirical studies in nonfinancial sectors have shown that the divergence between the ultimate shareholder's control and cash flow rights might be a better proxy, since it captures the net incentive of the ultimate shareholder to expropriate minority owners (e.g., Boubaker et al, 2014;Jiang et al, 2014). However, in our sample, banks with a higher level of control concentration in the ultimate shareholder have lower divergence (see Table 4 for more detail).…”
Section: Baseline Econometric Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Family owners with excess control rights can, for example, threaten to oust managers if they do not behave appropriately (Gomulya & Boeker, 2016). Moreover, studies show that shareholders with high levels of excess control are more knowledgeable about firm operations than those without excess control (Jiang et al, 2014;Liu & Magnan, 2011). This knowledge could facilitate their efforts to guard against fraudulent behavior.…”
Section: The Effect Of Excess Control Rights On Financial Misconductmentioning
confidence: 99%
“…More equity financing indicates more institutional ownership compared to debt financing. It is possible that institutional ownership would strengthen institutional monitoring (Jiang et al ., 2014; Appel et al ., 2016) and corporate governance. On the contrary, firms with lower institutional ownership have weak governance.…”
Section: Additional Analysesmentioning
confidence: 99%